Hipertexto e estratégias de leitura - Rissi, Gilse Cabrera (2009)
This dissertation, inserted in the Reading, Writing and Portuguese Language Teaching research field, is based on studies of the text in the socio-cognitive-interactional perspective and has as its purpose to contribute with the teaching of reading in digital context. To develop this study, a research was conducted with public and private high school students, in order to identify the hyper-readers profile and their strategies to read hypertexts. The results show that there are many strategies present on the hypertext reading, and among these we highlight: the maintenance of the objective, the use of prediction, the activation of previous knowledge, the use of inferences etc. It was also possible to realize that hyper-readers use adequate strategies to read texts in digital contexts, thanks to the knowledge they have about the hypertextual writing, ways of locating and accessing in the space provided by the internet. On the whole, the research data reveal the importance of working with hypertext during classes, starting from the previous knowledge students already have about navigating and exploring the internet oceans